SUSTAINABILITY APPLICATIONS OF CORNCOB ASH FOR COMPOSITE APPLICATIONS: A REVIEW: Corn cob ash - Oluwaseyi Omotayo, Taiwo; Frank, Okoyeh; Samuel-Mary, Obiorah; Somtochukwu, Ojiyi Binah; Darlington, Amadi (Universitas Ngeri Malang, 2025)
Environmental awareness about possible adverse effects has substantially expanded, and, consequently, recycling or utilizing agricultural and industrial waste by-products has become an increasingly desirable option for waste disposal. Corncob ash, a byproduct of agricultural processing, has gained attention in recent years for its potential as a sustainable material in composite applications. This review article provides an overview of the utilization of corncob ash in composite materials, focusing on its properties, influence on mechanical properties of composites, and environmental benefits. Additionally, challenges and future directions for the sustainable application of corncob ash in composite materials are addressed. Overall, this study underscores the increasing critical role of corn cob ash in advancing sustainability in composite production